Critique of The Repression of Palestinian Media in Arabic Caricatures on The Instagram Account @rahma_toons (A Piercean Semiotic Study) - Akhmad Firmansyah Firman; Arif Rahman Hakim (Modality Journal: International Journal of Linguistics and Literature, 2025)
This study addresses the central question of how five Arabic political caricatures posted by @rahma_toons account represent media repression against Palestinian journalists amid escalating violence in Gaza. The background to the issue stems from the increasing targeting of journalists and the limited number of visual semiotics studies that interpret the dynamics of violence through digital caricatures. The novelty of this research lies in the use of caricatures as visual texts to reveal epistemic repression, patterns of attacks on journalists, and approaches that are still rarely discussed in Middle Eastern media studies. The research questions are answered through descriptive qualitative methods using Charles Sanders Peirce's semiotic framework, which analyzes visual signs to reveal the dominant patterns of meaning embedded in caricatures. The analysis revealed three dominant patterns: journalists as marked targets, destruction of equipment as erasure of truth, and systematic silencing. These findings demonstrate that digital caricatures function as counter-narratives that expose structural violence and preserve collective memory when mainstream media channels are constrained.